Gen Z dan Keinginan Berwirausaha : Eksplorasi Peran Lingkungan Keluarga dan Akademis di Kota Makassar - Serdyla Dalatean; Deanella Ovanda Onis; Dewi Zahro Ardani; Yeyen Richandra; Monalisa Monalisa (FEB Universitas Sultan Ageng Tirtayasa, 2025)
Indonesia needs more young entrepreneurs to build a sustainable and competitive economy. This study examines the role of family support, entrepreneurship education, and self-efficacy in shaping entrepreneurial intention among Generation Z in Makassar City. This research uses quantitative methods with data collection through questionnaires involving 256 university students in Makassar. Data analysis was conducted using SmartPLS 4.0. The results showed that entrepreneurship education and self-efficacy have a significant influence on entrepreneurial intention, while family support did not show a significant influence. The implication of this study is the importance of increasing entrepreneurship education and strengthening self-efficacy in encouraging entrepreneurial interest among Generation Z.